1985
DOI: 10.1007/bf00706729
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial neoplasms in children in Ibadan, Nigeria

Abstract: Analysis of 89 intracranial tumors in children presenting at the University College Hospital, Ibadan, Nigeria, between 1960 and 1982 is reported. These tumors are commonest in the first decade of life and occur more in males than in females. Fifty-three per cent of the primary brain tumors are supratentorial. The commonest sites are cerebellum, cerebrum, and the pons. The common histological types are astrocytomas, medulloblastomas, ependymomas, and oligodendrogliomas. Craniopharyngiomas are among the most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
3

Year Published

1987
1987
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 12 publications
2
6
3
Order By: Relevance
“…This agrees with the findings of Aghadiuno et al (12) in children and of Jackson and Okubadejo (13) in adults.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This agrees with the findings of Aghadiuno et al (12) in children and of Jackson and Okubadejo (13) in adults.…”
Section: Discussionsupporting
confidence: 93%
“…Burkitt's lymphoma is a neoplasm primarily involving the jaw and abdomen of African children and is unusual in Caucasians(11). The higher incidence found in this study when compared to 10% found in a previous study (12) may reflect the present socio-economic climate in the country with the prohibitive cost of treatment, and therefore progression of the disease with brain involvement. Involvement of the brain is usually associated with widespread organ involvement and has a poor prognosis (11).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Previous reports suggest that craniopharyngiomas occur more frequently in children aged 5–14 years with a higher incidence in Asia and Africa [4,23,24,25]. Most of the investigations have stated that craniopharyngiomas rank next to medulloblastomas in their incidence rate [3,4,5, 10,14,15,16,17,18,19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…In different epidemiological investigations, the upper age limit of childhood varied from 14 to 17 years [3,4,5,14,15,16,17,18,19,20,21,22,23] and even to 21 years [2]; therefore, there may be statistical variation. For a detailed comparison with minor bias, we analyzed the data for the 0–14 and 0–17 age group separately.…”
Section: Discussionmentioning
confidence: 99%